Evidence for Cyclical Fractional Crystallization, Recharge, and Assimilation in Basalts of the Kimama Drill Core, Central Snake River Plain, Idaho: 5.5-Million-Years of Petrogenesis in a Mid-crustal Sill Complex - Potter, Katherine E.; Shervais, John W.; Christiansen, Eric H.; Vetter, Scott K. (Frontiers in Earth Science, 2018)
Basalts erupted in the Snake River Plain of central Idaho and sampled in the Kimama drill core link eruptive processes to the construction of mafic intrusions over 5.5 Ma. Cyclic variations in basalt composition reveal temporal chemical heterogeneity related to fractional crystallization and the assimilation of previously-intruded mafic sills. A range of compositional types are identified within 1912 m of continuous drill core: Snake River olivine tholeiite (SROT), low K SROT, high Fe-Ti, and evolved and high K-Fe lavas similar to those erupted at Craters of the Moon National Monument. Detailed lithologic and geophysical logs document 432 flow units comprising 183 distinct lava flows and 78 flow groups. Each lava flow represents a single eruptive episode, while flow groups document chemically and temporally related flows that formed over extended periods of time. Temporal chemical variation demonstrates the importance of source heterogeneity and magma processing in basalt petrogenesis. Low-K SROT and high Fe-Ti basalts are genetically related to SROT as, respectively, hydrothermally-altered and fractionated daughters. Cyclic variations in the chemical composition of Kimama flow groups are apparent as 21 upward fractionation cycles, six recharge cycles, eight recharge-fractionation cycles, and five fractionation-recharge cycles. We propose that most Kimama basalt flows represent typical fractionation and recharge patterns, consistent with the repeated influx of primitive SROT parental magmas and extensive fractional crystallization coupled with varying degrees of assimilation of gabbroic to ferrodioritic sills at shallow to intermediate depths over short durations. Trace element models show that parental SROT basalts were generated by 5-10% partial melting of enriched mantle at shallow depths above the garnet-spinel lherzolite transition. The distinctive evolved and high K-Fe lavas are rare. Found at four depths, 319 m, 1045 m, 1078 m, and 1189 m, evolved and high K-Fe flows are compositionally unrelated to SROT magmas and represent highly fractionated basalt, probably accompanied by crustal assimilation. These evolved lavas may be sourced from the Craters of the Moon/Great Rift system to the northeast. The Kimama drill core is the longest record of geochemical variation in the central Snake River Plain and reinforces the concept of magma processing in a layered complex.